Electronic Healthcare First International Conference, eHealth 2008, London, September 8-9, 2008, Revised Selected Papers - Weerasinghe, Dasun (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the First International Conference on Electronic Healthcare for the 21st century, eHealth 2008, held in London, UK, in September 2008. Organized as a meeting point for telecare product vendors, policy makers, government ministers, academics, clinicians and all those involved in electronic and mobile health the eHealth conference provides a forum to examine and to share ideas contributing to the advancement of telecare into the 21st century. The 21 revised full papers and 8 revised short papers presented together with 1 invited lecture were carefully reviewed and selected from the presentations at the conference. The papers cover various topics such as data mining for personalized healthcare services, healthcare supply chain management and implementing the electronic health record, diagnostics and intelligent real-time monitoring, human factors, policies, regulations and standards, interoperability solutions, security, privacy, trust and risk management, as well as novel telecare products. This volume is the first in the LNICST series that aims at serving the scientific community at large by deploying digital age access and use of information tools by putting knowledge in the service of digital economy and quality of life.